Pengaruh Upah Minimum Kabupaten Atau Kota (UMK), Pertumbuhan Ekonomi Dan Inflasi Terhadap Pengangguran Terbuka Di Jawa Tengah Tahun 2019 – 2023 - Bagus Kusuma Ardi; Selly Ananda Putri; Batista Sufa Kefi (sekolah Tinggi Ilmu Ekonomi Dharmaputra Semarang, 2025)
The purpose of this study was to analyze the effect of UMK, economic growth and inflation on open unemployment in Central Java in 2019-2023. The total population of this study consisted of 35 districts or cities that provided 175 observations of data and used the saturated sample method so that all were used as sample data. The analysis method used was multiple linear regression. Hypothesis testing using 5% degrees of freedom. The results of the reliability and validity tests showed that all question items were reliable and the constructs were valid, in addition, the regression had met the fit model. The results of the study showed that the Regency/City Minimum Wage (X1) had a significant positive effect on Open Unemployment (Y). Internal Control (X2) had a significant positive effect on employee performance (Y). Work motivation (X3) had a significant positive effect on employee performance (Y).